2011
DOI: 10.1111/j.1752-4571.2011.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive potential of ash (Fraxinus excelsior) populations against the novel emerging pathogenHymenoscyphus pseudoalbidus

Abstract: An emerging infectious pathogen Hymenoscyphus pseudoalbidus has spread across much of Europe within recent years causing devastating damage on European common ash trees (Fraxinus excelsior) and associated plant communities. The present study demonstrates the presence of additive genetic variation in susceptibility of natural F. excelsior populations to the new invasive disease. We observe high levels of additive variation in the degree of susceptibility with relatively low influence of environmental factors (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
99
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 51 publications
15
99
0
Order By: Relevance
“…Genetic analyses will be instrumental in devising strategies to cope with an increased pressure from established and new diseases as a result of better suitability of the climatic conditions and/or more intense and farreaching trade (Bawa and Dayanandan 1998;Archie et al 2008;Jombart et al 2011). For example, there is genetic evidence that some ash trees (Fraxinus excelsior) in Denmark are resistant against the emerging fungal pathogen Chalara fraxinea (McKinney et al 2011;Kjaer et al 2012), which is now reported to cause ash dieback throughout Europe, from Poland to France and from Sweden to Switzerland (Bengtsson et al 2012;Gross et al 2012). For this pathosystem, there are also data on the genetic variability of the pathogen in lowland vs. highland Poland (Kraj et al 2012) and in the Åland islands, mainland Finland, Estonia and Latvia (Rytkönen et al 2011).…”
Section: Interdisciplinarity Stakeholder Involvement and Trade-offsmentioning
confidence: 99%
“…Genetic analyses will be instrumental in devising strategies to cope with an increased pressure from established and new diseases as a result of better suitability of the climatic conditions and/or more intense and farreaching trade (Bawa and Dayanandan 1998;Archie et al 2008;Jombart et al 2011). For example, there is genetic evidence that some ash trees (Fraxinus excelsior) in Denmark are resistant against the emerging fungal pathogen Chalara fraxinea (McKinney et al 2011;Kjaer et al 2012), which is now reported to cause ash dieback throughout Europe, from Poland to France and from Sweden to Switzerland (Bengtsson et al 2012;Gross et al 2012). For this pathosystem, there are also data on the genetic variability of the pathogen in lowland vs. highland Poland (Kraj et al 2012) and in the Åland islands, mainland Finland, Estonia and Latvia (Rytkönen et al 2011).…”
Section: Interdisciplinarity Stakeholder Involvement and Trade-offsmentioning
confidence: 99%
“…European ash shows evident genetic variation in the level of susceptibility to shoot damage caused by H. fraxineus (Kirisits and Freinschlag 2012;Lobo et al 2014;McKinney et al 2011;Stener 2013), a feature that is inherited from parents to offspring (Kjaer et al 2012;Lobo et al 2015;Pliura et al 2011). The genetic mechanisms behind the differential field performance of individual trees in stands with epidemic levels of disease remain unknown.…”
Section: Future Prospects In Europe and North Americamentioning
confidence: 99%
“…Within clonal trials in Sweden (STENER, 2013) and Denmark (MCKINNEY et al, 2011a;KJAER et al, 2011) strong genetic control of resistance against ash dieback was found. This was based upon the observation of artificially or naturally infected trees in common garden experiments that have shown clonal differences in infection intensity (MCKINNEY et al, 2011b).…”
Section: Genetic Differences Between Susceptible and Less Susceptiblementioning
confidence: 99%
“…After observing that some individuals were less affected by the disease than others systematic investigations on the resistance against the disease were started (MCKINNEY et al, 2011a;PLIURA et al, 2011;KJAER et al, 2011;STENER, 2013). Such investigations include the question whether the lower susceptibility of certain individuals might be in relation to genetics.…”
Section: Genetic Analysis Of European Common Ash (Fraxinus Excelsior mentioning
confidence: 99%